Emerson B. Powery and Rodney S. Sadler, Jr., The Genesis of Liberation: Biblical Interpretation in the Antebellum Narratives of the Enslaved: Westminster John Knox Press, 2016 (Homiletic, 2019)
Please click the PDF button to access the review.